Electrolyte additive, electrolyte and lithium battery thereof
By using lithium tetraboride compounds as electrolyte additives in lithium metal batteries, a solvated structure and crosslinking network with anion enrichment are formed, which solves the problem of lithium dendrites and improves the cycle stability and safety of the battery.
Patent Information
- Application Number
- CN202510029096.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-08
- Publication Date
- 2025-04-15
AI Technical Summary
Lithium metal batteries are prone to form uneven lithium dendrites during charging, resulting in short circuits inside the battery, reduced cycle life and increased safety risks. The existing electrolyte additives are insufficient in inhibiting dendrites.
Lithium tetraphenylboride compounds are used as electrolyte additives to optimize the composition and proportion of the electrolyte to form a solvated structure and crosslinking network with anion enrichment, which enhances the mechanical strength of the electrolyte and promotes the uniform transmission of lithium ions.
Effectively inhibit the growth of lithium dendrites, improve the migration number and transmission rate of lithium ions, extend the cycle life of the battery and improve safety.
Smart Images

Figure BDA0005233636510000021 
Figure BDA0005233636510000041 
Figure BDA0005233636510000061
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium ion batteries, and in particular relates to an electrolyte additive, an electrolyte and a lithium battery thereof. Background Art
[0002] Lithium metal batteries are considered to be a strong contender for next-generation battery technology due to their high energy density, especially in the fields of electric vehicles and portable electronic devices. Compared with traditional graphite anode materials, lithium metal anodes can provide higher theoretical specific capacity (3860mAh / g vs. 372mAh / g for graphite), thereby significantly improving the energy density of batteries. However, despite these significant advantages of lithium metal anodes, they also face a series of serious challenges in practical applications, especially in the uniform deposition of lithium and the problem of dendrite growth.
[0003] Lithium dendrite formation is one of the main problems faced by lithium metal batteries. When lithium ions are deposited onto the negative electrode surface during battery charging, sharp lithium dendrites may form if the deposition is uneven. These dendrites can penetrate the separator and cause internal short circuits in the battery, which not only reduces the cycle life of the battery, but may also cause serious safety issues such as overheating, fire, and even explosion.
[0004] The formation of lithium dendrites is closely related to the chemical composition of the electrolyte. Researchers have tried a variety of methods, including the development of new electrolyte additives. These additives are designed to improve the deposition behavior of lithium ions on the surface of the negative electrode, thereby reducing the formation of dendrites. However, the ability of current electrolyte additives to inhibit the formation of lithium dendrites is still insufficient. Many additives may be effective in the early stages, but their effectiveness gradually weakens as the number of battery cycles increases. In addition, some additives may react with other components in the battery to generate the so-called "dead lithium" problem. Dead lithium refers to irreusable lithium formed by the incompletely reversible deposition of lithium ions on the surface of the negative electrode during battery cycling. This not only reduces the Coulombic efficiency of the battery, but may also further aggravate the formation of lithium dendrites.
[0005] Therefore, researching and optimizing a new electrolyte additive is crucial to improving battery performance and safety. Summary of the invention
[0006] The present invention aims at the problems in the prior art and discloses an electrolyte additive, an electrolyte and a lithium battery thereof; by preparing a new lithium tetraphenylborate compound additive and optimizing the components and proportions of the electrolyte, the synergistic effect can enhance the mechanical strength of the electrolyte and form a Li +The cross-linked network for transmission; the solvation structure of anion aggregation effectively promotes the transmission efficiency of lithium ions in the electrode material; it is especially suitable for high-voltage systems and improves the cycle stability and safety of the battery.
[0007] The present invention is achieved through the following technical solutions:
[0008] In a first aspect, the present invention provides an electrolyte additive, wherein the electrolyte additive comprises a lithium tetraphenylborate compound represented by a general structural formula I;
[0009]
[0010] Among them, R1, R2, R3, R4, R5, R6, R7, R8, R9, R 10 , R 11 , R 12 , R 13 , R 14 , R 15 Each independently selected from hydrogen atom, C1-C 10 Alkyl, C1-C 10 One of the following groups: alkoxy, nitro, hydroxyl, halogen, amino, aldehyde, carboxylate, and sulfonate.
[0011] As a further embodiment, R1, R2, R3, R4, R5, R6, R7, R8, R9, R 10 , R 11 , R 12 , R 13 , R 14 , R 15 Each is independently selected from a hydrogen atom, a C1-C5 alkyl group, a C1-C5 alkoxy group, a nitro group, and a hydroxyl group;
[0012] In the X-ray diffraction (XRD) measurement, characteristic peaks representing the structure of lithium tetraphenylborate are found at 10-11°, 11.5-13°, 14.5-15.3°, 17-18.3°, 18.5-19.4°, 20-21.5°, 24-26° and 26.7-27.6°, and there are also 5 Li-containing characteristic peaks in the range of 27.9-36°.
[0013] In a second aspect, the present invention provides an electrolyte, comprising the electrolyte additive described in the first aspect, a compound containing a polyol acrylate group, and a carbonate solvent; wherein the mass of the electrolyte additive accounts for 3-15% of the total mass of the electrolyte, the mass of the compound containing a polyol acrylate group accounts for 3-8% of the total mass of the electrolyte, and the mass of the carbonate solvent accounts for 60-85% of the total mass of the electrolyte.
[0014] As a further solution, the compound containing polyol acrylate groups is selected from one or more of multi-branched polyol acrylate compounds or linear polyol acrylate compounds; wherein the multi-branched polyol acrylate compound refers to a compound containing three or more branched polyol acrylates. As some exemplary examples; the multi-branched polyol acrylate compound is selected from one of pentaerythritol tetraacrylate and polydipentaerythritol hexaacrylate; the linear polyol acrylate compound is selected from one of polyethylene glycol diacrylate and polyethylene glycol dimethacrylate.
[0015] Furthermore, the compound containing a polyol acrylate group is preferably selected from compounds containing four or more branched polyol acrylates.
[0016] As a further embodiment, the electrolyte further includes a lithium salt; the lithium salt is selected from one or more of lithium hexafluorophosphate (LiPF6), lithium nitrate (LiNO3), lithium dioxalatoborate (LiBOB), lithium bis(trifluoromethanesulfonyl imide) (LiTFSI), lithium difluorooxalatoborate (LiDFOB), lithium isonicotinozone (LiISDN), and lithium isonicotinonitrile (LiISPN).
[0017] As a further solution, the ratio of the lithium salt to the lithium tetraphenylborate compound represented by the general structural formula I in the electrolyte is selected from one or more of 1:(0.2-0.5).
[0018] As a further scheme, the electrolyte preferably includes the electrolyte additive described in the first aspect, lithium salt, a compound containing a polyol acrylate group shown in the general structural formula II, and a carbonate solvent; wherein the mass of the electrolyte additive accounts for 4-5% of the total mass of the electrolyte, the mass of the lithium salt accounts for 12-14% of the total mass of the electrolyte, the mass of the compound containing a polyol acrylate group accounts for 4-5% of the total mass of the electrolyte, and the mass of the carbonate solvent accounts for 75-82% of the total mass of the electrolyte.
[0019] As a further embodiment, the carbonate solvent is selected from one or more of linear carbonate solvents and cyclic carbonate solvents; as some exemplary examples: the linear carbonate is selected from one or more of dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, and ethyl vinyl carbonate; the cyclic carbonate is selected from one or more of ethylene carbonate, vinyl ethylene carbonate, and 1,2-propylene glycol carbonate.
[0020] As a further solution, the carbonate solvent is preferably used in combination of ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate; the volume ratio of ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate is 1:1:1.
[0021] As a further embodiment, the electrolyte further includes an initiator; the initiator is selected from one or more of azobisisobutyronitrile, azobisisoheptanenitrile, dimethyl azobisisobutyrate, hydrogen peroxide, ammonium persulfate, potassium persulfate, benzoyl peroxide, tert-butyl benzoyl peroxide, and methyl ethyl ketone peroxide.
[0022] As a further solution, the mass of the initiator accounts for 0.1-0.3% of the total mass of the electrolyte;
[0023] In a third aspect, the present invention provides a method for preparing an electrolyte additive; the preparation method comprises: preparing an electrolyte additive according to a molar ratio of:
[0024] S1: placing a tetraphenylboric acid compound represented by the general structural formula III in an organic solvent and stirring the mixture at 40-50° C. for 1.5-2.5 h to obtain a solution A;
[0025] S2: placing lithium hydroxide in an organic solvent and stirring at 20-30° C. for 5-15 min to obtain a solution B;
[0026] S3: adding the solution B described in S2 dropwise to the solution A described in S1, maintaining the temperature at 40-50° C.; after precipitation is complete, performing post-treatment to obtain lithium tetraphenylborate compounds.
[0027] III
[0028]
[0029] As a further embodiment, R1, R2, R3, R4, R5, R6, R7, R8, R9, R 10 , R 11 , R 12 , R 13 , R 14 , R 15 Each independently selected from hydrogen atom, C1-C 10 Alkyl, C1-C 10 One of alkoxy, nitro, and hydroxyl groups; A + Selected from NH4 + 、Al 3+ and Mg 2+ One of them.
[0030] As a further solution, the mass of the organic solvent accounts for 70-90% of the total system mass.
[0031] As a further embodiment, the molar ratio is selected from tetraphenylboric acid compounds: lithium hydroxide = 1: (0.8-3.2).
[0032] As a further embodiment, the organic solvent is selected from one or more of ether solvents and ester solvents; ester solvents are preferred.
[0033] As a further embodiment, the ether solvent is selected from one or more of an ether solvent containing a hydroxyl group, an ether solvent containing a single ether bond, and an ether solvent containing a complex functional group; wherein the complex functional group is selected from C1-C 10 One or more of alkoxyl groups, olefins, and alkynes; as an illustrative example: the ether solvent containing a hydroxyl group is selected from one or more of dipropylene glycol butyl ether, ethylene glycol dimethyl ether, and propylene glycol monomethyl ether; the ether solvent containing a single ether bond is selected from one or more of cyclopentyl methyl ether, ethyl ether, and propyl ether; the ether solvent containing a complex functional group is selected from one or more of butynediol dipropoxy ether, propargyl ether, and propargyl ether.
[0034] As a further embodiment, the ester solvent is selected from one or more of linear carbonate solvents and cyclic carbonate solvents; as some exemplary examples: the linear carbonate is selected from one or more of dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, and ethyl vinyl carbonate; the cyclic carbonate is selected from one or more of ethylene carbonate and 1,2-propylene glycol carbonate.
[0035] As a further solution, the post-processing operation in S3 includes filtering and washing; the number of washing times is 3-5 times; and the washing solvent is selected from one of ether or ester solvents.
[0036] In a fourth aspect, the present invention provides a lithium battery and an energy storage device comprising the electrolyte described in the second aspect.
[0037] As a further solution, the lithium battery can adapt to an electrochemical window range selected from 0 to 5.5V.
[0038] The characteristics and beneficial effects of the present invention are:
[0039] (1) The electrolyte additive of the present invention has an anion-enriched solvation structure; it is beneficial to inhibit the growth of lithium dendrites; it reduces concentration polarization, thereby increasing the migration number of lithium ions and promoting the migration rate of lithium ions; at the same time, the electrolyte additive can also be used alone as a lithium salt; it ensures that the electrolyte has high ionic conductivity and improves the charge and discharge performance of the battery.
[0040] (2) By introducing a compound containing a polyol acrylate group, a polymerization reaction occurs with the electrolyte additive of the present invention to form a cross-linked structure, which can enhance the mechanical strength of the electrolyte and form a Li +At the same time, its acrylate group is also beneficial to improve the polymerization degree of its electrolyte and shorten the polymerization time; it effectively protects the electrode surface and reduces the side reactions between the electrolyte and the electrode, thereby extending the cycle life of the battery.
[0041] (3) The preparation method of the electrolyte additive of the present invention is simple, low-cost, easy to realize industrial production, and environmentally friendly, meeting the requirements of green chemistry;
[0042] (4) The lithium battery of the present invention has good electrochemical properties in a wide temperature range and is suitable for high-voltage systems; it has excellent stability; it is not prone to side reactions; thereby improving the cycle stability and safety of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0044] Figure 1 is an optical image of lithium tetraphenylborate prepared in Example 1 of the present invention;
[0045] Figure 2 is the X-ray diffraction pattern (XRD) of lithium tetraphenylborate prepared in Example 1 of the present invention;
[0046] Figure 3 This is the electrochemical window diagram of Example 1 of the present invention at 25°C;
[0047] Figure 4 is the ionic conductivity diagram of Example 1 of the present invention at 25°C;
[0048] Figure 5 is the ion migration number diagram of Example 1 of the present invention at 25°C;
[0049] Figure 6 This is a picture of the lithium metal surface of the batteries assembled in Example 1 of the present invention and Comparative Example 1 after 100 cycles. DETAILED DESCRIPTION
[0050] In order to facilitate the understanding of the present invention, the present invention will be described in more detail below, and embodiments of the present invention are given, but the scope of the present invention is not limited thereby.
[0051] In a first aspect, the present invention provides an electrolyte additive, wherein the electrolyte additive comprises a lithium tetraphenylborate compound represented by a general structural formula I;
[0052]
[0053] Among them, R1, R2, R3, R4, R5, R6, R7, R8, R9, R 10 , R 11 , R 12 , R 13 , R 14 , R 15 Each independently selected from hydrogen atom, C1-C 10 Alkyl, C1-C 10 One of alkoxy, nitro, hydroxyl, halogen, amino, aldehyde, carboxylate, and sulfonate groups;
[0054] In the X-ray diffraction (XRD) measurement, characteristic peaks representing the structure of lithium tetraphenylborate are found at 10-11°, 11.5-13°, 14.5-15.3°, 17-18.3°, 18.5-19.4°, 20-21.5°, 24-26° and 26.7-27.6°, and there are also 5 Li-containing characteristic peaks in the range of 27.9-36°.
[0055] In the existing technology, lithium dendrite growth and Li + The present invention studies and optimizes the components of the electrolyte and provides a new electrolyte additive, which is a lithium tetraphenylborate compound; the additive has a borate anion containing four benzene rings, and the π-π bond effect of the benzene ring and its larger mass and volume can make it move faster in the electrolyte than lithium ions (Li + ) is slow and has slow kinetics; the slow movement of anions helps to reduce concentration polarization, thereby increasing the migration number of lithium ions and promoting the migration rate of lithium ions. At the same time, the anion part contains four benzene ring structures, which can form stronger interactions with cations due to their large size and more electron clouds. This strong interaction helps to stabilize anions and promote the enrichment of anions in the electrolyte, which is conducive to the formation of anion-enriched solvation structure; and this solvation-enriched structure is conducive to the interfacial chemical reaction at the negative electrode of the battery, thereby producing a uniform, dense, and stable inorganic-rich SEI film, which is not only conducive to improving Li + The transport dynamics of lithium ions can be improved to achieve uniform lithium deposition. It is also beneficial to inhibit the growth of lithium dendrites, preventing the growth of lithium dendrites from causing serious volume expansion of the battery, resulting in a decrease in the battery's cycle stability and electrochemical performance. The boric acid groups it contains can form a stable solvation structure with the cations in the electrolyte, further stabilizing the ion environment in the electrolyte, reducing the desolvation barrier of lithium ions, and improving the ionic conductivity of the electrolyte.
[0056] As a further embodiment, R1, R2, R3, R4, R5, R6, R7, R8, R9, R 10 , R 11 , R 12 , R 13 , R 14 , R 15 Each is independently selected from a hydrogen atom, a C1-C5 alkyl group, a C1-C5 alkoxy group, a nitro group, and a hydroxyl group.
[0057] The smaller substituent groups within the preferred range are more conducive to adjusting the compound containing four benzene rings and boronic acid groups to have a higher solubility, which is conducive to uniform distribution in the electrolyte; in addition, its small molecular structure is more conducive to enhancing its chemical stability in the electrolyte, thereby further optimizing the electrochemical properties of the compound, so that it exhibits better compatibility and adaptability in the composition of the electrolyte.
[0058] In a second aspect, the present invention provides an electrolyte, comprising the electrolyte additive described in the first aspect, a compound containing a polyol acrylate group, and a carbonate solvent; wherein the mass of the electrolyte additive accounts for 3-15% of the total mass of the electrolyte, the mass of the compound containing a polyol acrylate group accounts for 3-8% of the total mass of the electrolyte, and the mass of the carbonate solvent accounts for 60-85% of the total mass of the electrolyte.
[0059] First, the electrolyte additive lithium tetraphenylborate compounds provided by the present invention can not only utilize the special structure of its anion part to promote the formation of a solvation structure of anion aggregation, thereby reducing the migration rate of anions and improving the transmission capacity of lithium ions; it can also be used alone as a lithium salt to provide lithium ions to ensure that the electrolyte has high ionic conductivity and improve the charge and discharge performance of the battery. Secondly, in the process of preparing the electrolyte, the present invention also selects a special compound containing a polyol acrylate group as a crosslinking agent for use in conjunction with lithium tetraphenylborate compounds. The crosslinking agent is formed by the polymerization of alcohols and acrylates. The alcohol group can undergo a polymerization reaction with the acrylate group to form a crosslinked structure. This structure can enhance the mechanical strength of the electrolyte while also forming a structure that is beneficial to Li + The benzene ring can form a stable structure with the acrylate group due to its stable chemical properties and the ability to form π-π conjugation, which helps to improve the mechanical strength and conductivity of the electrolyte; the alcohol group forms hydrogen bonds with the benzene ring to further enhance the thermal stability of the electrolyte; it helps to enhance the Li + transmission.
[0060] In addition, the interaction between the C=C double bond contained in its acrylate group and the polyphenyl rings in the lithium tetraphenylborate compound is beneficial to improving the polymerization degree of its electrolyte and shortening the polymerization time; the compound containing polyol acrylate groups also has good flexibility. When used in conjunction with lithium tetraphenylborate compounds, it can maintain a certain fluidity and fully penetrate into the battery, and also has a high stability. This stability helps to reduce the decomposition and deterioration of the electrolyte during the battery charging and discharging process, thereby extending the battery life.
[0061] As a further solution, the compound containing polyol acrylate groups is selected from one or more of multi-branched polyol acrylate compounds or linear polyol acrylate compounds; wherein the multi-branched polyol acrylate compound refers to a compound containing three or more branched polyol acrylates. As some exemplary examples; the multi-branched polyol acrylate compound is selected from one of pentaerythritol tetraacrylate and polydipentaerythritol hexaacrylate; the linear polyol acrylate compound is selected from one of polyethylene glycol diacrylate and polyethylene glycol dimethacrylate.
[0062] In polyol acrylate compounds containing multiple branches, the fine structure of the branches, such as multiple acrylate flexible conductive groups, has a significant effect on the ionic conductivity, is more conducive to synergistic effect with large-volume tetraphenylboric acid compounds, and has high compatibility, thereby improving the ionic conductivity of the electrolyte.
[0063] Furthermore, the compound containing a polyol acrylate group is preferably selected from compounds containing four or more branched polyol acrylates.
[0064] As a further embodiment, the electrolyte further includes a lithium salt; the lithium salt is selected from one or more of lithium hexafluorophosphate (LiPF6), lithium nitrate (LiNO3), lithium dioxalatoborate (LiBOB), lithium bis(trifluoromethanesulfonyl imide) (LiTFSI), lithium difluorooxalatoborate (LiDFOB), lithium isonicotinozone (LiISDN), and lithium isonicotinonitrile (LiISPN).
[0065] As a further solution, the ratio of the lithium salt to the lithium tetraphenylborate compound represented by the general structural formula I in the electrolyte is selected from one or more of 1:(0.2-0.5).
[0066] By using lithium tetraphenylborate compounds and lithium salts in combination and regulating their mutual proportion, it helps to avoid the limitations of lithium tetraphenylborate compounds when used alone. It can ensure the solvation effect of anion aggregation in the solution and promote the migration rate of lithium ions. It can also further increase the lithium concentration in the electrolyte solution and improve the ion conductivity by adding lithium salts, thereby significantly improving the cycle stability and rate performance of the battery.
[0067] As a further scheme, the electrolyte preferably includes the electrolyte additive described in the first aspect, lithium salt, a compound containing a polyol acrylate group shown in the general structural formula II, and a carbonate solvent; wherein the mass of the electrolyte additive accounts for 4-5% of the total mass of the electrolyte, the mass of the lithium salt accounts for 12-14% of the total mass of the electrolyte, the mass of the compound containing a polyol acrylate group accounts for 4-5% of the total mass of the electrolyte, and the mass of the carbonate solvent accounts for 75-82% of the total mass of the electrolyte.
[0068] As a further embodiment, the carbonate solvent is selected from one or more of linear carbonate solvents and cyclic carbonate solvents; as some exemplary examples: the linear carbonate is selected from one or more of dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, and ethyl vinyl carbonate; the cyclic carbonate is selected from one or more of ethylene carbonate, vinyl ethylene carbonate, and 1,2-propylene glycol carbonate.
[0069] The present invention selects carbonates as electrolyte solvents, mainly utilizing the good compatibility of their ester groups with compounds containing polyol acrylate groups and lithium tetraphenylborate compounds, thereby ensuring that the components in the electrolyte have better solubility; at the same time, carbonate solvents have higher chemical stability than other ester and non-ester solvents, and are not easy to chemically react with other components in the electrolyte, thereby ensuring the long-term stability of the electrolyte.
[0070] As a further solution, the carbonate solvent is preferably used in combination of ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate; the volume ratio of ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate is 1:1:1.
[0071] By selecting a combination of cyclic carbonates and linear carbonates, high chemical stability and fluidity can be obtained at the same time; it is beneficial to reduce the viscosity of the electrolyte, and can fully embed the network structure formed by the cross-linking polymerization of tetraphenylborate lithium compounds and compounds containing polyol acrylate groups, reduce the diffusion barrier of lithium ions, and promote the transmission rate of lithium ions.
[0072] As a further embodiment, the electrolyte further includes an initiator; the initiator is selected from one or more of azobisisobutyronitrile, azobisisoheptanenitrile, dimethyl azobisisobutyrate, hydrogen peroxide, ammonium persulfate, potassium persulfate, benzoyl peroxide, tert-butyl benzoyl peroxide, and methyl ethyl ketone peroxide.
[0073] As a further solution, the mass of the initiator accounts for 0.1-0.3% of the total mass of the electrolyte;
[0074] In a third aspect, the present invention provides a method for preparing an electrolyte additive; the preparation method comprises: preparing an electrolyte additive according to a molar ratio of:
[0075] S1: placing a tetraphenylboric acid compound represented by the general structural formula III in an organic solvent and stirring the mixture at 40-50° C. for 1.5-2.5 h to obtain a solution A;
[0076] S2: placing lithium hydroxide in an organic solvent and stirring at 20-30° C. for 5-15 min to obtain a solution B;
[0077] S3: adding the solution B described in S2 dropwise to the solution A described in S1, maintaining the temperature at 40-50° C.; after precipitation is complete, performing post-treatment to obtain lithium tetraphenylborate compounds.
[0078] III
[0079]
[0080] As a further embodiment, R1, R2, R3, R4, R5, R6, R7, R8, R9, R 10 , R 11 , R 12 , R 13 , R 14 , R 15 Each independently selected from a hydrogen atom, a C1-C 10 Alkyl, C1-C 10 One of alkoxy, nitro, and hydroxyl groups; A + Selected from NH4 + 、Al 3+ and Mg 2+ One of them.
[0081] As a further solution, the mass of the organic solvent accounts for 70-90% of the total system mass.
[0082] As a further embodiment, the molar ratio is selected from tetraphenylboric acid compounds: lithium hydroxide = 1: (0.8-3.2).
[0083] As a further solution, the organic solvent is selected from one or more of ether solvents and ester solvents; ester solvents are preferred. Ester solvents can provide good solubility and reaction medium, which helps to evenly mix the tetraphenylboric acid compound and lithium hydroxide used in the present invention, thereby improving the reaction efficiency. In addition, ester solvents have good chemical stability, which helps to maintain the selectivity of the reaction, reduce unnecessary by-products, and improve the purity of the target product.
[0084] As a further embodiment, the ether solvent is selected from one or more of an ether solvent containing a hydroxyl group, an ether solvent containing a single ether bond, and an ether solvent containing a complex functional group; wherein the complex functional group is selected from C1-C 10 One or more of alkoxyl groups, olefins, and alkynes; as an illustrative example: the ether solvent containing a hydroxyl group is selected from one or more of dipropylene glycol butyl ether, ethylene glycol dimethyl ether, and propylene glycol monomethyl ether; the ether solvent containing a single ether bond is selected from one or more of cyclopentyl methyl ether, ethyl ether, and propyl ether; the ether solvent containing a complex functional group is selected from one or more of butynediol dipropoxy ether, propargyl ether, and propargyl ether.
[0085] As a further embodiment, the ester solvent is selected from one or more of linear carbonate solvents and cyclic carbonate solvents; as some exemplary examples: the linear carbonate is selected from one or more of dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, and ethyl vinyl carbonate; the cyclic carbonate is selected from one or more of ethylene carbonate and 1,2-propylene glycol carbonate.
[0086] As a further solution, the post-processing operation in S3 includes filtering and washing; the number of washing times is 3-5 times; and the washing solvent is selected from one of ether or ester solvents.
[0087] In a fourth aspect, the present invention provides a lithium battery and an energy storage device comprising the electrolyte described in the second aspect. The electrolyte used in the battery of the present invention is particularly suitable for high-voltage systems and is not prone to decomposition side reactions, thereby improving the cycle stability and safety of the battery. Under high-voltage systems, the electrolyte of the present invention has excellent stability through a specific combination of additives and solvents, effectively inhibiting the decomposition of the electrolyte under high voltage and extending the service life of the battery.
[0088] As a further solution, the lithium battery can adapt to an electrochemical window range selected from 0 to 5.5V.
[0089] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.
[0090] The chemical raw materials involved in the following examples and comparative examples are all prior art and are commercially available. The experimental devices, test devices, etc. involved in the following examples and comparative examples are all conventional devices in the art, without special requirements and limitations.
[0091] Example 1
[0092] Preparation of electrolyte additives:
[0093] Add 20 mL of dimethyl carbonate (DMC) to a round-necked flask with a thermometer, weigh 6.745 g of 99.9% pure tetraphenylammonium borate and add it to the flask, and stir at 45°C for 2 h (solution A);
[0094] Take a clean beaker and add 10 mL of dimethyl carbonate (DMC) therein, weigh 0.479 g of lithium hydroxide with a purity of 99.9% and add it to the beaker, and stir at 25° C. for 10 min (solution B).
[0095] Solution B was slowly added dropwise to solution A and continued to stir at 45°C. Stirring was then stopped, the system was filtered, and the filter cake was washed three times with dimethyl carbonate (DMC), and the filtrate was collected.
[0096] 7g of carbon tetrachloride was added to the filtrate under stirring, and a white precipitate gradually precipitated in the solution. After the addition of carbon tetrachloride was completed, the solution was stirred at room temperature for 30 minutes, and then the system was filtered and the obtained white powder was dried to obtain the product lithium tetraphenylborate. The yield was 89.7% and the purity was 99.2%.
[0097] Preparation of electrolyte:
[0098] In a glove box filled with argon, ethylene carbonate (EC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC) were mixed in a volume ratio of 1:1:1 to obtain 15.544 g of a mixed solution, and 2.564 g of lithium hexafluorophosphate (LiPF6) and 0.906 g of lithium tetraphenylborate (Li-TPB) were slowly added to the mixed solution and stirred to obtain a mixed solution;
[0099] 0.954 g of polydipentaerythritol hexaacrylate (DPHA) was added to the above mixed solution, and after stirring evenly, 0.032 g of azobisisobutyronitrile (AIBN) was added, and stirred for 10 minutes to mix evenly to obtain an electrolyte solution.
[0100] Battery Assembly:
[0101] The above electrolyte solution and metallic lithium were used as negative electrodes, and NCM811 (>15 mg / cm2) was used as positive electrodes to prepare Li||NCM811 full batteries. All operations were performed in a glove box filled with argon.
[0102] The prepared battery was allowed to stand at 25°C for 12 h and then placed in an oven and heated at 60°C until a solid-state lithium metal battery was obtained.
[0103] Example 2
[0104] The specific steps and methods are the same as those in Example 1. The difference is:
[0105] Preparation of electrolyte additives:
[0106] Add 20 mL of ethylene glycol dimethyl ether (DME) to a round-necked flask with a thermometer, weigh 6.745 g of 99.9% pure ammonium tetraphenylborate and add it to the flask, and stir at 45°C for 2 h (solution A);
[0107] Take a clean beaker and add 10 mL of ethylene glycol dimethyl ether (DME) therein, weigh 0.479 g of lithium hydroxide with a purity of 99.9% and add it to the beaker, and stir at room temperature for 10 min (solution B).
[0108] Slowly add solution B into solution A and continue stirring until precipitation is complete, and keep the stirring temperature at 45°C. Then stop stirring and filter the system to collect the white precipitate.
[0109] The collected white precipitate was washed three times with ethylene glycol dimethyl ether and the obtained white powder was dried to obtain the product lithium tetraphenylborate with a yield of 85.2% and a purity of 95.4%.
[0110] Example 3
[0111] The specific steps and methods are the same as those in Example 1; the difference is that:
[0112] Preparation of electrolyte:
[0113] In a glove box filled with argon, ethylene carbonate (EC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC) were mixed at a volume ratio of 1:1:1 to obtain 16.282 g of a mixed solution, and 2.686 g of Li-TPB was slowly added to the mixed solution and stirred to obtain a mixed solution;
[0114] 0.998 g of polydipentaerythritol hexaacrylate (DPHA) was added to the above mixed solution, and after stirring evenly, 0.034 g of azobisisobutyronitrile (AIBN) was added, and stirred for 10 minutes to mix evenly to obtain an electrolyte solution.
[0115] Example 4
[0116] The specific steps and methods are the same as those in Example 1; the difference is that:
[0117] Preparation of electrolyte:
[0118] In a glove box filled with argon, ethylene carbonate (EC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC) were mixed in a volume ratio of 1:1:1 to obtain 15.662 g of a mixed solution, and 2.498 g of lithium hexafluorophosphate (LiPF6) and 0.842 g of Li-TPB were slowly added to the mixed solution and stirred to obtain a mixed solution;
[0119] 0.976 g of polyethylene glycol dimethacrylate (PEGDMA) was added to the above mixed solution, and after stirring evenly, 0.022 g of azobisisobutyronitrile (AIBN) was added, and stirred for 10 min to mix evenly to obtain an electrolyte solution.
[0120] Example 5
[0121] The specific steps and methods are the same as those in Example 1; the difference is that:
[0122] Preparation of electrolyte:
[0123] In a glove box filled with argon, ethylene carbonate (EC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC) were mixed in a volume ratio of 1:1:1 to obtain 15.544 g of a mixed solution, and 2.664 g of lithium hexafluorophosphate (LiPF6) and 1.021 g of Li-TPB were slowly added to the mixed solution and stirred to obtain a mixed solution;
[0124] 1.596 g of polydipentaerythritol hexaacrylate (DPHA) was added to the above mixed solution, and after stirring evenly, 0.032 g of azobisisobutyronitrile (AIBN) was added, and stirred for 10 minutes to mix evenly to obtain an electrolyte solution.
[0125] Example 6
[0126] The specific steps and methods are the same as those in Example 1. The difference is that:
[0127] Preparation of electrolyte:
[0128] In a glove box filled with argon, 2.564 g of lithium hexafluorophosphate (LiPF6) and 0.906 g of Li-TPB were slowly added to 15.544 g of vinyl ethylene carbonate and stirred to obtain a mixed solution;
[0129] 0.954 g of polydipentaerythritol hexaacrylate (DPHA) was added to the above mixed solution, and after stirring evenly, 0.032 g of azobisisobutyronitrile (AIBN) was added, and stirred for 10 minutes to mix evenly to obtain an electrolyte solution.
[0130] Example 7
[0131] The specific steps and methods are the same as those in Example 1. The difference is that:
[0132] Preparation of electrolyte:
[0133] In a glove box filled with argon, ethylene carbonate (EC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC) were mixed at a volume ratio of 1:1:1 to obtain 15.544 g of a mixed solution, and 2.564 g of lithium bistrifluoromethanesulfonyl imide (LiTFSI) and 0.906 g of Li-TPB were slowly added to the mixed solution and stirred to obtain a mixed solution;
[0134] 0.954 g of polydipentaerythritol hexaacrylate (DPHA) was added to the above mixed solution, and after stirring evenly, 0.032 g of azobisisobutyronitrile (AIBN) was added, and stirred for 10 minutes to mix evenly to obtain an electrolyte solution.
[0135] Example 8
[0136] The specific steps and methods for preparing the electrolyte additive and the electrolyte are the same as those in Example 1, except that ammonium tetraphenylborate is replaced with magnesium tetraphenylborate. The yield is 88.2% and the purity is 99.1%.
[0137] Example 9
[0138] Add 20 mL of dimethyl carbonate (DMC) to a round-necked flask with a thermometer, weigh 6.129 g of 99.9% pure tetraphenylammonium borate and add it to the flask, and stir at 45°C for 2 h (solution A);
[0139] Take a clean beaker and add 10 mL of dimethyl carbonate (DMC) therein, weigh 0.871 g of lithium hydroxide with a purity of 99.9% and add it to the beaker, and stir at 25° C. for 10 min (solution B).
[0140] Solution B was slowly added dropwise to solution A and continued to stir at 45°C. Stirring was then stopped, the system was filtered, and the filter cake was washed three times with dimethyl carbonate (DMC), and the filtrate was collected.
[0141] 7g of carbon tetrachloride was added to the filtrate under stirring, and a white precipitate gradually precipitated in the solution. After the addition of carbon tetrachloride was completed, the solution was stirred at room temperature for 30 minutes, and then the system was filtered and the obtained white powder was dried to obtain the product lithium tetraphenylborate. The yield was 82.7% and the purity was 99.2%.
[0142] Comparative Example 1
[0143] The specific steps and preparation method are the same as those in Example 1, except that:
[0144] Preparation of electrolyte:
[0145] In a glove box filled with argon, ethylene carbonate (EC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC) were mixed in a mass ratio of 1:1:1 to obtain 16.282 g of a mixed solution, 2.686 g of lithium hexafluorophosphate (LiPF6) was slowly added to the mixed solution and stirred to obtain a mixed solution;
[0146] 0.998 g of polydipentaerythritol hexaacrylate (DPHA) was added to the above mixed solution, and after stirring evenly, 0.034 g of azobisisobutyronitrile (AIBN) was added, and stirred for 10 minutes to mix evenly to obtain an electrolyte solution.
[0147] Comparative Example 2
[0148] The specific steps and preparation method are the same as those in Example 1, except that:
[0149] Preparation of electrolyte:
[0150] In a glove box filled with argon, ethylene carbonate (EC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC) were mixed in a mass ratio of 1:1:1 to obtain 15.544 g of a mixed solution, and 2.564 g of lithium hexafluorophosphate (LiPF6) and 0.906 g of lithium nitrate (LiNO3) were slowly added to the mixed solution and stirred to obtain a mixed solution;
[0151] 0.954 g of polydipentaerythritol hexaacrylate (DPHA) was added to the above mixed solution, and after stirring evenly, 0.032 g of azobisisobutyronitrile (AIBN) was added, and stirred for 10 minutes to mix evenly to obtain an electrolyte solution.
[0152] Comparative Example 3
[0153] The specific steps and preparation method are the same as those in Example 1, except that:
[0154] Preparation of electrolyte:
[0155] In a glove box filled with argon, 15.344 g of ethylene carbonate (EC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC) were mixed in a mass ratio of 1:1:1 to obtain a mixed solution, and 2.564 g of lithium hexafluorophosphate (LiPF6) and 0.906 g of Li-TPB were slowly added to the mixed solution and stirred to obtain a mixed solution;
[0156] 2.154 g of polydipentaerythritol hexaacrylate (DPHA) was added to the above mixed solution, and after stirring evenly, 0.032 g of azobisisobutyronitrile (AIBN) was added and stirred for 10 minutes to mix evenly to obtain an electrolyte solution.
[0157] Comparative Example 4
[0158] The specific steps and preparation method are the same as those in Example 1, except that: 0.954 g of dicumyl peroxide (DCP) is added to the above mixed solution, stirred evenly, and then 0.032 g of azobisisobutyronitrile (AIBN) is added, and stirred for 10 minutes to mix evenly to obtain an electrolyte solution.
[0159] Comparative Example 5
[0160] The specific steps and preparation method are the same as those in Example 1, except that:
[0161] Preparation of electrolyte:
[0162] In a glove box filled with argon, 2.564 g of lithium hexafluorophosphate (LiPF6) and 0.906 g of Li-TPB were slowly added to 15.544 g of triethyl phosphate (TEP) and stirred to obtain a mixed solution;
[0163] 0.954 g of polydipentaerythritol hexaacrylate (DPHA) was added to the above mixed solution, and after stirring evenly, 0.032 g of azobisisobutyronitrile (AIBN) was added, and stirred for 10 minutes to mix evenly to obtain an electrolyte solution.
[0164] Specific test methods and conditions:
[0165] (1) Take 3 mg of the prepared lithium tetraphenylborate and measure XRD with a scanning range of 5-60° and a scanning rate of 5° / min.
[0166] (2) The electrolytes in each embodiment were used to assemble SS||SS batteries using stainless steel sheets as positive and negative electrodes; Li||SS batteries were assembled using metal lithium as negative electrodes and stainless steel as positive electrodes; Li||Li symmetric batteries were prepared using metal lithium as positive and negative electrodes; and Li||NCM811 full batteries were prepared using metal lithium as negative electrodes and NCM811 (>15 mg / cm2) as positive electrodes. All operations were performed in a glove box filled with argon.
[0167] (3) The prepared various batteries were placed at 25°C for 12 hours and then heated at 60°C in an oven for 6 hours to obtain solid-state lithium metal batteries.
[0168] (4) The electrochemical window of the electrolyte was determined by linear voltammetry (LSV). The assembled Li||SS battery was used as the test battery, and the electrochemical window was obtained by slowly scanning from the battery open circuit voltage to the positive voltage at a scanning rate of 1 mV s-1.
[0169] (5) Electrochemical impedance spectroscopy (EIS) was used to measure the electrolyte ion conductivity. The assembled SS||SS battery was used as the test battery for electrochemical impedance spectroscopy, with a frequency range of 0.1-10-6 Hz and an amplitude of 10 mV. After the test, the battery was disassembled to measure the thickness of the solid electrolyte, and the electrolyte ion conductivity was calculated based on the EIS results.
[0170] (6) Electrochemical impedance spectroscopy (EIS) and electrochemical impedance spectroscopy (CA) were used to determine the ion migration number. The assembled Li||Li battery was used as the test battery, the frequency range was 0.1-10-6 Hz, and the scan rate was 10 mV / s.
[0171] (7) Take Li||NCM811 full battery as the battery to be tested, at 0.52mAh / cm 2 The battery was charged and discharged cycled at a current density of to explore the battery stability.
[0172] Table 1
[0173]
[0174] Table 2 Preparation of solid-state lithium metal batteries
[0175]
[0176]
[0177] It can be seen from the examples and comparative examples as well as the data in Table 1 and Table 2 that the electrolyte prepared by the present invention has a lower polymerization time and good electrochemical performance and cycle stability. This indicates that the electrolyte additive prepared by the present invention can promote the uniform deposition of lithium ions and effectively inhibit the growth of lithium dendrites; it is beneficial to improve the charge and discharge efficiency of the battery and extend the cycle life of the battery. In addition, by comparing the experimental data, it can be clearly seen that the electrolyte additive of the present invention can not only be used as a single lithium salt, but also can maintain good electrochemical performance when used in combination with different lithium salts, which indicates that the electrolyte additive of the present invention has good compatibility and applicability.
[0178] It can be seen from Examples 1-9 and Comparative Examples 1 and 2 that although the electrochemical performance of Comparative Example 2 is improved compared with that of Comparative Example 1, the cross-linking polymerization time of Comparative Examples 1 and 2 is longer than that of the examples, and the electrochemical performance and cycle life are worse than those of the examples. This is because in the examples, the lithium tetraphenylborate compounds of the present invention have a multi-benzene ring structure, which can be used in conjunction with polyol acrylates containing two or more, and the C=C double bond thereof can be used to interact with the benzene ring molecules to shorten the polymerization time, thereby avoiding uneven ion distribution caused by excessive polymerization time, forming a concentration gradient, and increasing the transmission barrier of lithium ions, thereby causing a decrease in the electrochemical performance of the battery.
[0179] It can be seen from Examples 1-9 and Comparative Example 3 that when two or more polyol acrylate crosslinkers within a suitable range are used in combination with lithium tetraphenylborate compounds, the proportion within the suitable range helps them to exert the best synergistic effect; while in Comparative Example 3, when the proportion of the crosslinker is relatively high relative to the embodiment, the capacity retention rate of the battery is lower than that of the embodiment; this is because when the proportion of polyol acrylate is too high, the intermolecular interaction is enhanced, resulting in a too tight crosslinking network, which limits the migration path of lithium ions and cannot effectively inhibit the growth of lithium dendrites; thus affecting the capacity retention rate of the battery. In addition, polyol acrylates with a higher content have stronger flexibility, which is not conducive to achieving a balance with the rigid structure of multiple benzene rings of lithium tetraphenylborate compounds, thereby affecting the overall mechanical properties and electrochemical stability of the battery.
[0180] It can be seen from Examples 1-9 and Comparative Example 4 that, compared with Examples 1-9, when other types of cross-linking agents are used, the polymerization time of the electrolyte is too long compared with that of the examples. This is because the polyol acrylate cross-linking agents selected in the present invention containing two or more C=C double bonds can interact strongly with the benzene rings of lithium tetraphenylborate compounds, thereby promoting the polymerization time; in addition, the cross-linking agent selected in the present invention has a wider cross-linking network and better flexibility, and a stable connection can be formed between the acrylate and the benzene ring, which is conducive to forming a uniform ion transport channel and promoting the generation of solvation enrichment phenomenon, thereby being conducive to having good mechanical stability while also having a higher ion migration rate.
[0181] It can be seen from Examples 1-9 and Comparative Example 5 that when preparing the electrolyte, compared with Examples 1-9, the comparative example selected triethyl phosphate as the solvent component of the electrolyte; it can be seen from Table 1 that the electrochemical performance of its electrolyte has decreased. This is because phosphate electrolytes are unstable relative to carbonate solvents, and are easily decomposed during the charge and discharge process, generating gas, which affects the safety and stability of the battery; at the same time, the conductivity of phosphate electrolytes is relatively low, and it is easy to affect the electrochemical properties such as battery rate during the battery charge and discharge cycle. In contrast, the carbonate solvents used in the present invention have good compatibility with compounds containing polyol acrylate groups and lithium tetraphenylborate compounds, can form a stable solvation structure, effectively improve the ionic conductivity of the electrolyte, and reduce the volatilization of the solvent, ensuring the stable performance of the battery during long-term use.
[0182] It can be seen from Table 1 and Example 1, Example 5 and Example 3 that the electrolyte additive provided by the present invention can also be used alone as a lithium salt, and it can also obtain a good capacity retention rate. This is because the cationic part of the electrolyte additive of the present invention is a lithium salt, which can supplement lithium ions and promote ion transmission; at the same time, the anionic part of the additive of the present invention is a borate ion part containing four benzene rings, and the large volume of its benzene ring and the π-π bond molecular structure have slow dynamics, which are conducive to promoting the formation of solvation enrichment, thereby reducing the desolvation barrier of lithium ions; and realizing the rapid transmission of lithium ions. Therefore, when it is used alone as a lithium salt, it can still maintain the stable performance of the battery. In addition, by comparing Example 1, Example 5, and Example 3, we can also find that when the electrolyte additive of the present invention is compounded with a specific type of lithium salt within an optimized proportion range, the cycle performance and capacity retention rate of the battery can be further optimized. This shows that there is a synergistic effect between the electrolyte additive of the present invention and the specific lithium salt, which can more effectively promote the embedding and deintercalation process of lithium ions in the electrode material, thereby improving the overall performance of the battery.
[0183] pass Figure 1 It can be seen from the optical image that the prepared lithium tetraphenylborate is a white powder. Figure 2 In the X-ray diffraction (XRD) measurement, obvious characteristic peaks indicating the structure of lithium tetraphenylborate appeared at 10-11°, 11.5-13°, 14.5-15.3°, 17-18.3°, 18.5-19.4°, 20-21.5°, 24-26° and 26.7-27.6°. In addition, 5 Li-containing characteristic peaks appeared in the range of 27.9-36°. After analysis, it can be determined that the prepared material is lithium tetraphenylborate.
[0184] pass Figure 3 It can be seen that the prepared solid electrolyte can reach an electrochemical window of 5.26V at room temperature and can be adapted to high-voltage batteries;
[0185] pass Figure 4 It can be seen that the prepared solid electrolyte can reach 1.51x10 -4 S cm -1 The ionic conductivity of
[0186] pass Figure 5 It can be seen that the prepared solid electrolyte can achieve an ion migration number of 0.65 at room temperature;
[0187] pass Figure 6It can be seen that the lithium metal surface of the battery assembled with the electrolyte containing Li-TPB is smoother and brighter, while the lithium metal surface of the battery assembled with the electrolyte not containing Li-TPB shows more black and uneven deposits, indicating that the electrolyte containing Li-TPB can achieve more uniform lithium deposition.
[0188] It should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. An electrolyte additive, comprising a lithium tetraphenylborate compound represented by the general structural formula I; in, R1, R2, R3, R4, R5, R6, R7, R8, R9, R 10 , R 11 , R 12 , R 13 , R 14 , R 15 Each independently selected from a hydrogen atom, a C1-C 10 Alkyl, C1-C 10 One of alkoxy, nitro, hydroxyl, halogen, amino, aldehyde, carboxylate, and sulfonate groups; In the X-ray diffraction (XRD) measurement, characteristic peaks representing the structure of lithium tetraphenylborate are found at 10-11°, 11.5-13°, 14.5-15.3°, 17-18.3°, 18.5-19.4°, 20-21.5°, 24-26° and 26.7-27.6°, and there are also 5 Li-containing characteristic peaks in the range of 27.9-36°.
2. An electrolyte additive according to claim 1, characterized in that: In the general structural formula I, R1, R2, R3, R4, R5, R6, R7, R8, R9, R 10 , R 11 , R 12 , R 13 , R 14 , R 15 Each is independently selected from a hydrogen atom, a C1-C5 alkyl group, a C1-C5 alkoxy group, a nitro group, and a hydroxyl group.
3. An electrolyte, characterized in that: The electrolyte comprises the electrolyte additive according to any one of claims 1-2, a compound containing a polyol acrylate group, and a carbonate solvent; wherein the mass of the electrolyte additive accounts for 3-15% of the total mass of the electrolyte, the mass of the compound containing a polyol acrylate group accounts for 3-8% of the total mass of the electrolyte, and the mass of the carbonate solvent accounts for 60-85% of the total mass of the electrolyte.
4. The electrolyte according to claim 3, characterized in that The compound containing polyol acrylate groups is selected from one or more of multi-branched polyol acrylate compounds or linear polyol acrylate compounds; wherein the multi-branched polyol acrylate compound is selected from one of pentaerythritol tetraacrylate and polydipentaerythritol hexaacrylate; the linear polyol acrylate compound is selected from one of polyethylene glycol diacrylate and polyethylene glycol dimethacrylate; Furthermore, the compound containing a polyol acrylate group is preferably selected from compounds containing four or more branched polyol acrylates.
5. The electrolyte according to claim 3, characterized in that The electrolyte further comprises a lithium salt; the lithium salt is selected from one or more of lithium hexafluorophosphate (LiPF6), lithium nitrate (LiNO3), lithium bis(oxalatoborate) (LiBOB), lithium bis(trifluoromethanesulfonylimide) (LiTFSI), lithium difluorooxalatoborate (LiDFOB), lithium isonicotinohydrazone (LiISDN), and lithium isonicotinonitrile (LiISPN); Furthermore, the ratio of the lithium salt to the lithium tetraphenylborate compound represented by the general structural formula I in the electrolyte is selected from one or more of 1:(0.2-0.5).
6. The electrolyte according to claim 3, characterized in that The electrolyte preferably comprises the electrolyte additive according to any one of claims 1 to 2, a lithium salt, a compound containing a polyol acrylate group as shown in the general structural formula II, and a carbonate solvent; wherein the mass of the electrolyte additive accounts for 4-5% of the total mass of the electrolyte, the mass of the lithium salt accounts for 12-14% of the total mass of the electrolyte, the mass of the compound containing a polyol acrylate group accounts for 4-5% of the total mass of the electrolyte, and the mass of the carbonate solvent accounts for 75-82% of the total mass of the electrolyte.
7. The electrolyte according to claim 3, characterized in that The carbonate solvent is selected from one or more of linear carbonate solvents and cyclic carbonate solvents; wherein the linear carbonate is selected from one or more of dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, and ethyl ethylene carbonate; the cyclic carbonate is selected from one or more of ethylene carbonate, ethylene ethylene carbonate, and 1,2-propylene glycol carbonate; The electrolyte further includes an initiator; the initiator is selected from one or more of azobisisobutyronitrile, azobisisoheptanenitrile, dimethyl azobisisobutyrate, hydrogen peroxide, ammonium persulfate, potassium persulfate, benzoyl peroxide, tert-butyl benzoyl peroxide, and methyl ethyl ketone peroxide; Furthermore, the mass of the initiator accounts for 0.1-0.3% of the total mass of the electrolyte; Furthermore, the carbonate solvent is preferably selected from the group consisting of ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate in combination; the volume ratio of ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate is 1:1:
1.
8. A method for preparing the electrolyte additive according to any one of claims 1 to 2; characterized in that: The preparation method comprises: according to the molar ratio: S1: placing a tetraphenylboric acid compound represented by the general structural formula III in an organic solvent and stirring the mixture at 40-50° C. for 1.5-2.5 h to obtain a solution A; S2: placing lithium hydroxide in an organic solvent and stirring at 20-30° C. for 5-15 min to obtain a solution B; S3: adding the solution B described in S2 dropwise to the solution A described in S1, maintaining the temperature at 40-50° C.; after precipitation is complete, performing post-treatment to obtain lithium tetraphenylborate compounds. III 9. The method for preparing the electrolyte additive according to claim 8, characterized in that: In the general structural formula III, R1, R2, R3, R4, R5, R6, R7, R8, R9, R 10 , R 11 , R 12 , R 13 , R 14 , R 15 Each independently selected from a hydrogen atom, a C1-C 10 Alkyl, C1-C 10 One of alkoxy, nitro, and hydroxyl groups; A + Selected from NH4 + 、Al 3+ and Mg 2+ One of; Furthermore, the mass of the organic solvent accounts for 70-90% of the total system mass; Further, the molar ratio is selected from tetraphenylboric acid compound: lithium hydroxide = 1: (0.8-3.2); Furthermore, the organic solvent is selected from one or more of ether solvents and ester solvents; Furthermore, the post-processing operation in S3 includes filtering and washing; wherein the number of washing times is 3-5 times; and the washing solvent is selected from one of ether or ester solvents; Furthermore, the ether solvent is selected from one or more of ether solvents containing hydroxyl groups, ether solvents containing a single ether bond, and ether solvents containing complex functional groups; wherein the complex functional group is selected from C1-C 10 One or more of alkoxy, olefin, and alkyne; the ether solvent containing hydroxyl group is selected from one or more of dipropylene glycol butyl ether, ethylene glycol dimethyl ether, and propylene glycol monomethyl ether; the ether solvent containing a single ether bond is selected from one or more of cyclopentyl methyl ether, ethyl ether, and propyl ether; the ether solvent containing a complex functional group is selected from one or more of butynediol dipropoxy ether, propargyl ether, and propargyl ether; Furthermore, the ester solvent is selected from one or more of linear carbonate solvents and cyclic carbonate solvents; wherein the linear carbonate is selected from one or more of dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, and ethyl vinyl carbonate; and the cyclic carbonate is selected from one or more of ethylene carbonate and 1,2-propylene glycol carbonate.
10. A lithium battery or energy storage device comprising the electrolyte additive according to any one of claims 1 to 2 or the electrolyte according to any one of claims 3 to 7; Furthermore, the lithium battery can adapt to an electrochemical window range selected from 0 to 5.5V.
Citation Information
Cited By
Battery monomer and preparation method thereof, battery device and energy storage device
CN122068113A